2020
DOI: 10.1515/hmbci-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

The effects of circuit resistance training on plasma progranulin level, insulin resistance and body composition in obese men

Abstract: BackgroundProgranulin (PGRN) is implicated in obesity and insulin resistance (IR). The aim of this study was to evaluate the effects of 8 weeks of circuit resistance training (CRT) on plasma PGRN, IR and body composition in obese men.Materials and methodsTwenty-eight healthy obese men [age: 36 ± 7.7 years, body weight (BW): 96.4 ± 15.6 kg, body mass index (BMI): 32.4 ± 4.5 kg/m2] completed the study. Subjects were randomly assigned to two groups of control and training. Subjects in the training group underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Similar results were reported by another study after 12-weeks of CT with very high intensity (≥ 75% of HRmax) in obese and overweight females [21]. In addition, studies demonstrated no changes in fasting glucose levels following an 8-week resistance CT (3 times per week, 50-85% of 1-RM) in obese men [38], or following HCT protocol of only 4 weeks [22]. On the other hand, 2 studies which used only resistance CT demonstrated reductions in blood lipid markers in obese men (3 weekly sessions, 65-85% of 1RM) [36] and in obese overweight women (3-4 weekly sessions of 15 resistance exercise stations, 10-12 repetitions per station performed at 70-80% of HRR) after 8 weeks [33].…”
Section: Biochemical Markerssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were reported by another study after 12-weeks of CT with very high intensity (≥ 75% of HRmax) in obese and overweight females [21]. In addition, studies demonstrated no changes in fasting glucose levels following an 8-week resistance CT (3 times per week, 50-85% of 1-RM) in obese men [38], or following HCT protocol of only 4 weeks [22]. On the other hand, 2 studies which used only resistance CT demonstrated reductions in blood lipid markers in obese men (3 weekly sessions, 65-85% of 1RM) [36] and in obese overweight women (3-4 weekly sessions of 15 resistance exercise stations, 10-12 repetitions per station performed at 70-80% of HRR) after 8 weeks [33].…”
Section: Biochemical Markerssupporting
confidence: 88%
“…Other studies used circuit resistance/weight training in obese individuals, mostly in women [33][34][35][36][37][38] and reported varying results regarding body composition, muscular strength, and biochemical markers. Some other studies compared different CT protocols [25,[39][40][41] in this population with varying results, but most of them highlighted the superiority of higher intensities, in the changes of body composition.…”
mentioning
confidence: 99%
“…After excluding 1080 records due to their irrelevance to the research question, 1657 were considered eligible for full‐text assessment (Figure 1). A total of 116 articles 24–139 describing 114 independent trials were included in this systematic review and meta‐analysis with 23 articles examining children or adolescents, 24–46 30 articles examining young adults, 47–76 38 articles examining middle‐aged adults,…”
Section: Resultsmentioning
confidence: 99%
“…CharacteristicsA total of 2537 participants with overweight/obesity participated in the included studies: 506 young adults (median age = 23.6 yr, interquartile range [IQR] = 21.2 to 27.0 yr; median BMI = 28.5 kg•m −2 , IQR = 26.8 to 31.8 kg•m −2 ; and body fat percentage = 32.9%, IQR = 28.7% to 36.1%)103), 901 middle-age adults (median age = 44.5, IQR = 38.1 to 53.6 yr; median BMI = 29.9 kg•m −2 , IQR = 28.6 to 31.7 kg•m −2 ; and body fat percentage = 40.1%, IQR = 30.7% to 44.8%)(25,26,(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)105,106), and 1130 older adults (median age = 68.2 yr, IQR = 65.9 to 69.1 yr; median BMI = 29.4 kg•m −2 , IQR = 27.6 to 31.6 kg•m −2 ; and body fat percentage = 38.0%, IQR = 36.1% to 42.6%)(22,28,32,(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)…”
mentioning
confidence: 99%